Epidemiological trends of malaria in an endemic district Tumkur, Karnataka - Krishna, Chandana; Haradanhalli, Ravish Shankaraiah (International Journal Of Community Medicine And Public Health, 2017)
Background: Efforts to control and eliminate malaria are high-impact strategic investments that generate significant returns for public health. In this regard, Government of India, launched NVBDCP in 2002, to control the disease. Since then, India has demonstrated significant achievements in malaria control with a progressive decline in total cases and deaths. Overall, malaria cases have consistently declined from 2 million in 2001 to 1.1 million cases in 2015. The decline in number of cases varied from region to region. In this background, the present study was conducted to know the trend of malaria in one of the endemic district Tumkur of Karnataka state. Methods: A case record analysis was done for the past 15 years (2001-2015) from the available data at district malaria office of Tumkur district and the data was analysed. Results: The present study showed that there is a gradual decline in the malaria cases from 27,553 in 2001 to 68 in 2015 and no deaths have been reported. The number of outbreaks is also declining with no outbreaks in the last 3 years. The present study also showed a seasonal trend in occurrence of malaria with increased incidence during June-October months. Conclusions: The trend in malaria cases is gradually declining, indicating that it is progressing towards malaria control and with sustained efforts, malaria can be reduced substantially and elimination can be achieved by 2030.